2020
DOI: 10.23850/23899573.3232
|View full text |Cite
|
Sign up to set email alerts
|

Características sensoriales de granos y licor de cacao por un panel de jueces en entrenamiento

Abstract: El Centro de Atención al Sector Agropecuario del SENA, regional Santander cuenta con un laboratorio de análisis sensorial y un panel de jueces en entrenamiento para catacion de cacao. La región Santandereana es la mayor zona productora de cacao de Colombia, durante el proceso de transformación de cacao se presentan defectos de los granos, siendo estos los causantes de la perdida de las características de los nibs de cacao para obtener un licor de cacao de calidad y a su vez lo desvaloriza. Se hace necesario re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…The sensory evaluation revealed that, in all sites and days of fermentation, cocoa notes obtained intensity scores higher than 6, however, our results contrast with those reported by Calvo et al [16] who found values below 5 in cocoa samples from three different regions in Colombia. Also, Romero and Pabón [75] mentions that beans with high cocoa flavor intensity indicate a successful processing (fermentation and drying), although the main attributes are mostly influenced by genotype [76]. In fermentation and drying, pyrazine contents increase because they are compounds of thermal origin and increase with increasing temperature [77], some studies mention that pyrazines are related to cocoa flavor [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensory evaluation revealed that, in all sites and days of fermentation, cocoa notes obtained intensity scores higher than 6, however, our results contrast with those reported by Calvo et al [16] who found values below 5 in cocoa samples from three different regions in Colombia. Also, Romero and Pabón [75] mentions that beans with high cocoa flavor intensity indicate a successful processing (fermentation and drying), although the main attributes are mostly influenced by genotype [76]. In fermentation and drying, pyrazine contents increase because they are compounds of thermal origin and increase with increasing temperature [77], some studies mention that pyrazines are related to cocoa flavor [8].…”
Section: Discussionmentioning
confidence: 99%
“…and Pabón [75] mentions that beans with high cocoa flavor intensity indicate a successful processing (fermentation and drying), although the main attributes are mostly influenced by genotype [76]. In fermentation and drying, pyrazine contents increase because they are compounds of thermal origin and increase with increasing temperature [77], some studies mention that pyrazines are related to cocoa flavor [8].…”
Section: Sensory Profilementioning
confidence: 99%